Alterations in the gut microbiome with hemorrhagic transformation in experimental stroke. (30th September 2021) - Huang, Qin; Di, Liao; Yu, Fang; Feng, Xianjing; Liu, Zeyu; Wei, Minping; Luo, Yunfang; Xia, Jian
Abstract: Objective: Hemorrhagic transformation (HT) is a life‐threatening complication of stroke. Whether changes in gut microbial composition underlie the development of HT remains unknown. This study aimed to investigate whether the gut microbiota is altered in HT rats and examine the association between these changes and inflammatory responses. Methods: HT was successfully established in rats injected with 50% glucose (6 ml/Kg, i.p.) 15 min before middle cerebral artery occlusion (MCAO, 90 min occlusion) with reperfusion. After 5 days, rats were euthanized, and their brains used to estimate infarct volume. The inflammatory factors, the analysis of gut microbiota, and short‐chain fatty acids (SCFA) were assessed. Results: In contrast with non‐HT rats, gut microbiota sequencing showed an elevation in the relative abundance of Proteobacteria and Actinobacteria in HT rats. Total SCFAs, especially butyrate and valeric acid, were significantly lower in the cecal contents of HT rats than in those of non‐HT rats. Hyperglycemia‐induced HT exacerbation was not observed when rats were treated with antibiotics, suggesting that altered microbiota play a critical role in hyperglycemic HT pathogenesis. Furthermore, rats whose gut was colonized with HT rat microbiota showed increased susceptibility to HT. Conclusion: This study provides important information about the gut microbiota profiles and SCFA levels of MCAO rats with HT or non‐HT. The susceptibility to HT in MCAO rats is associated with inflammation and gut microbiota modulation. Abstract : The gut microbiota modulates the inflammatory response and MMP9 that are associated with hemorrhagic transformation after stroke. Hemorrhagic transformation (HT) leads to gut dysbiosis and the inflammatory response. The changes of gut microbiota, peripheral inflammation, and SCFAs may further regulate MMP9 level and affect blood‐brain barrier permeability, contributing to an increase in HT susceptibility after stroke. MCAO rats that received fecal microbiota transplantation (FMT) of the "HT microbiota" exhibited high risk of HT.